Find the sum
tan ( a ) tan ( 2 a ) + tan ( 2 a ) tan ( 3 a ) + ⋯ + tan ( 8 a ) tan ( 9 a ) ,
where a = 5 π .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very creative. Nicely done.
We note that:
tan 5 π = − tan 5 4 π = tan 5 6 π = − tan 5 9 π tan 5 2 π = − tan 5 3 π = tan 5 7 π = − tan 5 8 π tan 5 5 π = tan π = 0
Therefore,
f ( a ) = tan 5 π tan 5 2 π + tan 5 2 π tan 5 3 π + tan 5 3 π tan 5 4 π + . . . tan 5 8 π tan 5 9 π = tan 5 π tan 5 2 π − tan 2 5 2 π + tan 5 π tan 5 2 π + 0 + 0 + tan 5 π tan 5 2 π − tan 2 5 2 π + tan 5 π tan 5 2 π = 4 tan 5 π tan 5 2 π − 2 tan 2 5 2 π
Since 5 π + 5 2 π + 5 2 π = π , there are three angles of a triangle.
⇒ tan 5 π tan 2 5 2 π = tan 5 π + 2 tan 5 2 π tan 5 π tan 2 5 2 π = tan 5 π + 1 − tan 2 5 π 4 tan 5 π ⇒ tan 2 5 2 π = 1 + 1 − tan 2 5 π 4 = 1 − tan 2 5 π 5 − tan 2 5 π
⇒ f ( a ) = 4 tan 5 π tan 5 2 π − 2 tan 2 5 2 π = 1 − tan 2 5 π 8 tan 2 5 π − 1 − tan 2 5 π 1 0 − 2 tan 2 5 π = 1 − tan 2 5 π 1 0 tan 2 5 π − 1 0 = − 1 0
Good job with chasing down all of these trigo terms.
Though, given how nice the answer is, one does wonder if there is an alternative approach. For example, we have ∑ i = 0 2 tan 3 i π tan 3 ( i + 1 ) π = − 3 and ∑ i = 0 6 tan 7 i π tan 7 ( i + 1 ) π = − 7 .
Write tana as a difference of numbers like tan(2a-a) and expand it accordingly now yoiu will get the value if 1+ (tan2atana)and by this you can find values of other as tana is in the denominator all the other terms cancels out leaving only tan9a and tana then by some manipulations you'll get -10
Nice work.
Similar to the explanation of @Adarsh Kumar.
Note that tan x tan y = tan ( x − y ) tan x − tan y − 1 Therefore, we have k = 1 ∑ 8 tan k α tan ( k + 1 ) α = k = 1 ∑ 8 ( tan α tan ( k + 1 ) α − tan k α − 1 ) = tan α tan 9 α − tan α − 8 Since 1 0 α = 2 π , it holds that tan 9 α = − tan α . Now we can get the answer: tan α tan 9 α − tan α − 8 = tan α − 2 tan α − 8 = − 1 0
Problem Loading...
Note Loading...
Set Loading...
We have that, tan a = 1 + tan ( n + 1 ) a × tan a n tan ( n + 1 ) a − tan n a ⟹ 1 + tan ( n + 1 ) a tan n a = tan a tan ( n + 1 ) a − tan n a ⟹ ( 1 + tan a tan 2 a ) + ( 1 + tan 2 a tan 3 a ) + . . . ( 1 + tan 8 a tan 9 a ) = tan a tan 2 a − tan a + tan 3 a − tan 2 a + . . . tan 9 a − tan 8 a = tan a tan 9 a − tan a = tan a − 2 tan a = − 2 ⟹ our answer is − 2 − 8 = − 1 0 .And done!